POLITIK MEDIA INTERNASIONAL - Abdul Rani Usman (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2018)
Political issues on International media play significant roles in shaping world opinion. The world today is influence by the superpower of United State, so that the political campaign of United Stated president candidates broadcasted all over the world. The political battle between Donald Trump and Hillary Clinton is unnerved watched by people all over the universe. The world famous medias such as CNN, New Yorks Time and others were fully covered their campaign process. Indonesian newspaper such as Analisa, Medan, North Sumatera also covered the campaign of the United State president’s candidate.Analisa is a newspapers that has huge readers in Sumatera. The readers come from wide range of different religion, culture, class and economic background. The political news that published by Analisa considered positive and able to develop a pluralism nation such as Indonesia. This research conducted at Analisa used Critical Discourse Analysis (CDA) method. The research carried out during October 2016. The news that researcher analyzed were world news in page two on daily basis. The specific news was about the campaign of the United State president candidate for 2017-2022. Most of the issues that mentioned by the candidates are about racism, religion, gender and the miss used of West Superpower, America-Europa and East, Russia-China Middle East. America seem is reluctant the China and Russia to be future super power states.